2020
DOI: 10.1371/journal.pntd.0008850
|View full text |Cite
|
Sign up to set email alerts
|

The function of peroxisome proliferator-activated receptors PPAR-γ and PPAR-δ in Mycobacterium leprae-induced foam cell formation in host macrophages

Abstract: Leprosy is a chronic infectious disease caused by Mycobacterium leprae ( M . leprae ). In lepromatous leprosy (LL), skin macrophages, harboring extensive bacterial multiplication, gain a distinctive foamy appearance due to increased intracellular lipid load. To determine the mechanism by which M . leprae modifies the lipid homeostasis in host cells, an in vitro M . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In addition to GPAT3, PPARγ also targets ADRP [39], which has a similar induction following M. leprae infection in THP-1 cells [6]. Recently, we have reported that activation of PPARγ and PPARδ is important for lipid accumulation in M. leprae-infected THP-1 cells [40]. In Schwann cells, phenolic glicolipid-1 (PGL-1) of M. leprae promoted lipid droplet formation by activating crosstalk between CD206 and PPARγ [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to GPAT3, PPARγ also targets ADRP [39], which has a similar induction following M. leprae infection in THP-1 cells [6]. Recently, we have reported that activation of PPARγ and PPARδ is important for lipid accumulation in M. leprae-infected THP-1 cells [40]. In Schwann cells, phenolic glicolipid-1 (PGL-1) of M. leprae promoted lipid droplet formation by activating crosstalk between CD206 and PPARγ [41].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have reported that activation of PPARγ and PPARδ is important for lipid accumulation in M . leprae -infected THP-1 cells [ 40 ]. In Schwann cells, phenolic glicolipid-1 (PGL-1) of M .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to host-derived biomarkers, a few studies have investigated the components or derivatives of M. leprae for leprosy diagnosis and monitoring of treatment efficacy (136)(137)(138)(139). Specifically, M. leprae antigenic determinants have been demonstrated in dermal macrophages and SCs during T1R (38).…”
Section: Leprae and Its Derivativesmentioning
confidence: 99%
“…The observed effects are blocked by PPAR-α antagonists and absent in PPAR-α-deficient mice. Recently, we found that PPAR-γ and PPAR-δ are activated in M. leprae -infected macrophages [ 22 ]. Infection with a recombinant strain of M. bovis BCG that produces phenolic glycolipid-1 (PGL-1) of M. leprae activates PPAR-γ in primary cultures of human Schwann cells [ 23 ].…”
Section: Activation Of Ppars By Mycobacteriamentioning
confidence: 99%
“…Recently, in M. leprae -infected THP-1 cells, we reported that the increased expression of PPAR-γ and PPAR-δ coincided with the induction of intracellular lipid droplet formation [ 22 ]. Further, the expression of the PPAR-γ target genes ADRP , scavenger receptor CD36 , fatty acid-binding protein 4 ( FABP4 ), and apolipoprotein C-1 ( APOC1 ) were significantly increased.…”
Section: Emerging Roles Of Ppars In Lipid Metabolism During Mycobactementioning
confidence: 99%